CODE SWITCHING IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOM - Rizky Yolanda (VISION, 2020)
EFL is a foreign language abbreviation for English. This is mainly used to talk about students (whose first language is not English) learning English while living in their own country. In the EFL classroom , the teacher usually switches the code to make students understand what the teacher is saying. The aim of this article is to present the use and functions of code switching in the classroom of the EFL. The subject of this study was English for a nursing class with 30 students and an English lecturer at Sultan Agung University Semarang. The activity was recorded in this EFL classroom for about 90 minutes and the code switching functions were analyzed on the basis of Hyme's (1962) framework. The study suggests that the use of code switching and mother tongue would facilitate the learning of foreign languages. Mother tongue could therefore be an important and useful element to help learners learn a foreign language during the learning process.